Coffee Skin Processing Becoming Organic Fertilizer in Belantih Village, Kintamani District, Bangli - Yohanes Parlindungan Situmeang; I Dewa Nyoman Sudita; I Ketut Selamat (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
Accelerated fermentation of coffee husk waste with the help of a fermenter and molasses solution for a certain time can produce compost which is an organic fertilizer product that provides added value and economic benefits for the community. Compost fertilizer when applied to soil can retain nutrients and water, increase the life of microorganisms in the soil and improve soil fertility and crop yields. This service in Belantih Village is carried out through training, counseling, mentoring, and technology transfer practices. The purpose of PKM is to obtain a composting technology package and strengthen group business management that is optimal and integrated with available natural resources. In this Community Partnership Program activity, the process of making compost based on coffee husk waste was introduced with simple fermentation technology. The community's response was very good to service activities at the Widya Pertiwi Women's Farmer Group. This can be seen from the enthusiasm of the participants or the number of questions submitted to the extension team regarding composting technology and its benefits for agriculture. The resulting compost can be applied to agricultural soils to improve soil physical properties which overall restore soil fertility. Considering the benefits and potential of coffee husk raw materials are very abundant, the prospect of developing organic compost fertilizer is very good in the future. The results obtained from this community service are in the form of a technology package for making compost organic fertilizer based on coffee skin waste and improving management through optimal group institutional strengthening and integration with available natural resources.